1995
DOI: 10.1177/002076409504100407
|View full text |Cite
|
Sign up to set email alerts
|

Family Pathology and Anorexia in the Indian Context

Abstract: Frequent associations have been found between family interaction and anorectic behaviour. Family theorists have viewed anorexia as a manifestation of a dysfunctional family system. We report three families of cases of anorexia (one male and two female) where the symptom was a reflection of family pathology and was being maintained by it. The cases emphasize the need to assess families of anorectics in detail and view them in the cultural context of eating.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 21 publications
1
11
0
Order By: Relevance
“…[1] In fact, a healthy body weight was considered as symbol of nurturance and good family life. [6] Our case further confirms the changing concept of Anorexia nervosa in India, and how imitation of western lifestyle is affecting our society. We have to be more vigilant about this new “culture change syndrome”, and educate individuals that “being slim” and the “size-zero fad” should not be blindly considered as a sign of attractiveness.…”
supporting
confidence: 75%
“…[1] In fact, a healthy body weight was considered as symbol of nurturance and good family life. [6] Our case further confirms the changing concept of Anorexia nervosa in India, and how imitation of western lifestyle is affecting our society. We have to be more vigilant about this new “culture change syndrome”, and educate individuals that “being slim” and the “size-zero fad” should not be blindly considered as a sign of attractiveness.…”
supporting
confidence: 75%
“…Two third of the group did very well or moderately well. [50] Later studies have reported improvement with family therapy in patients with a wide range of psychiatric problems, including schizophrenia,[51] alcohol dependence,[52] eating disorders,[53] epileptic psychosis,[54] adolescent conduct disorder,[55] marital problems,[56–59] family violence[6061] and in families coping with people living with HIV AIDS. [62]…”
Section: Understanding Psychotherapy From the Family Perspectivementioning
confidence: 99%
“…Carson and Chowdhury (2000) have effectively documented the necessity for family therapy in India. In addition, we would like to highlight that India is seeing an increase in rates of suicide, homicide, rape, and psychiatric related problems (Agarwal, Mehta, & Gupta, 1978;Chandra et al, 1995;Davar, 1999) in part because of the stresses of modern day life. India is second only to China in a ranking of nations by total number of suicides (Khan, 2002) with the highest rates of suicides occurring in the age groups of 20-30 years (Venkoba, 1984).…”
Section: Need For Family Therapy In Indiamentioning
confidence: 99%